Metallothioneins pattern during ontogeny of coastal dolphin, Pontoporia blainvillei, from Argentina - Polizzi, Paula Sabrina (2014)
Metallothioneins are signals of metal exposure and widely used in biomonitoring. Franciscana dolphin is an endemic cetacean from the Southwestern Atlantic Ocean, classified as Vulnerable A3d by the IUCN. Metallothionein, copper and zinc in Franciscana were assessed in two geographic groups; one inhabits La Plata River estuary, anthropogenically impacted, and the other inhabits marine coastal ecosystems, with negligible pollution. Despite the environment, hepatic and renal MT concentrations were similar, but there was a declining trend from early to later developmental stages. Metallothionein K/L, Cu and Zn levels corresponded to normal reported ranges. MT was not related with Cd. Fetal concentrations were higher than its mother. These results and the health status of dolphins are suggesting that MT correspond to physiological ranges for the species, and they are closely to homeostasis of Zn and Cu, according to its ontogenetic changes. The information constitutes the first MT information on Franciscana dolphin and can be considered as baseline for the species conservation.